2009
DOI: 10.1007/s00455-009-9258-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic Surrogate for Pharyngeal Strength: The Pharyngeal Constriction Ratio (PCR)

Abstract: The pharyngeal constriction ratio (PCR), derived directly from videofluoroscopy without the need for manometry, requires validation as a surrogate for pharyngeal strength. A correlation of −0.70 was previously identified between PCR and pharyngeal clearing pressures (PP) on separate fluoroscopic and manometric studies. As PP increases, PCR decreases. The objective of the current study was to evaluate the correlation between PCR and PP in 25 patients undergoing simultaneous fluoroscopy and pharyngeal manometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 12 publications
2
95
2
Order By: Relevance
“…Generalization of the current results to studies on healthy subjects should therefore be done with caution. In addition, the present results may not apply directly to other aspects of swallowing kinematics such as measurement of the pharyngeal constriction ratio [27], which involves an area measurement rather than a distance measurement.…”
Section: Discussionmentioning
confidence: 87%
“…Generalization of the current results to studies on healthy subjects should therefore be done with caution. In addition, the present results may not apply directly to other aspects of swallowing kinematics such as measurement of the pharyngeal constriction ratio [27], which involves an area measurement rather than a distance measurement.…”
Section: Discussionmentioning
confidence: 87%
“…All outcome measures were calculated by a speech language pathologist (SLP) with extensive experience in the objective assessment of videofluoroscopic swallow studies. 11,12,[18][19][20]24 The SLP was removed from the statistical analysis of the data and was blind to the patient diagnosis and cricopharyngeus muscle dysfunction grouping. Thus, any misclassification bias should be nondifferential and bias the investigation toward the null hypothesis of no association between CPD and pharyngeal dilation and weakness.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR is a surrogate marker of pharyngeal strength determined on fluoroscopy. 18,19 Previous studies have determined that the PCR increases as pharyngeal strength decreases. 18,19 The secondary outcome measures for this experiment were pharyngeal area in the lateral fluoroscopic view and PES opening.…”
Section: Methodsmentioning
confidence: 98%
“…The PCR has been validated with manometry and has therefore been suggested as a surrogate method for measuring pharyngeal strength [4]. Additionally, it has been shown that higher PCR measures, indicating poor constriction, are associated with aspiration [5].…”
Section: Introductionmentioning
confidence: 99%